Structure, stability and bonding in the 1Au10 clusters (2012)
A stochastic exploration of the quantum conformational space for the 1Au10 system using a modified Metropolis acceptance test afforded 15 stable configurations in the MP2/SDDALL potential energy surface -- The global minimum is predicted to be a 3D structure with D2d symmetry -- Topological analyses of the electron densities suggest that bonding appears to be of intermediate character, with substantial contributions from both covalent and closed shell interactions and that there is a direct correlation between the topological complexity of the electron density and cluster stability -- Evidence regarding the nature of the interactions is gathered from many sources, including the total number of delocalized electrons (nde), a novel covalency index -- Localization indices and condensed Fukui functions predict higher electron populations on peripheral, lowly coordinated atoms